Modelling of microhardness values by means of artificial neural networks of AL/SiCP metal matrix composite material couples processed with diffusion method - Taşkin, Mustafa; Çahgülü, U?ur (Association for Scientific Research, 2006)
In this study, modelling of microhardness values by means of artificial neural networks of Al/SiCp metal matrix composite material couples with diffusion method and manufactured by powder metallurgy process, were obtained using a backpropagation neural network that uses gradient descent learning algorithm. After diffusion bonding and relevant test, to prepare the training and test (checking) set of the network, results were recorded in a file on a computer. Then, the neural network was trained using the prepared training set. At the end of the training process, the test data were used to check the system accuracy. As a result the neural network was found successful in the prediction of modelling of microhardness values of Al/SiCp metal matrix composite material couples processed with diffusion method and behavior. © Association for Scientific Research.
Keywords: Artificial neural network; Diffusion bonding; Microhardness; MMCs